Validation of Land Fragmentation and Rural Sustainability Assessment Scale - et. al., Abba Saleh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted to assess the validity of land fragmentation and rural sustainability assessment scale (LFRSS). To achieve the purpose a cross-sectional survey design was adopted with a sample of 40 selected from local governments in Yobe State Nigeria. The instruments contained 71 items spread among the 3 constructs of land fragmentation, causes of land fragmentation and rural sustainability. The data collected was entered into Microsoft Excel 2016 and SPSS 25 was used for the Analysis. The scale was evaluated through content validity with experts and Reliability with Cronbach’s Alpha technique. The results indicated that, the scale has substantial content validity and acceptable reliability values of 0.77 (land fragmentation), 0.74 (causes of land fragmentation) and 0.75 (rural sustainability). However,8 items on the overall failed to satisfied the condition to be certified as valid and thus, entirely removed form the scale (4 in causes of land fragmentation and 4 in rural sustainability). Accordingly, with the satisfaction of measurement requirements by 63 items, it can be concluded that, the developed LFRSS validated in this study can be used to assess the extent of land fragmentation and rural sustainability in Yobe state Nigeria.